Efektifitas Terapi Yoga pada Stress Kerja Perawat Jiwa - Muhammad Iqbal Martani; Iyus Yosep (Syntax Corporation Indonesia, 2022)
Work stress is a pattern of psychological, emotional, cognitive and behavioral reactions to several aspects of work, work organization, and work environment Every workplace always contains various potential hazards that can affect the health of the workforce or can cause occupational diseases. This disorder can be a physical or psychic disturbance to the workforce. The purpose of this review is to find out the effectiveness of therapy in mental nurses who experience work stress. The method used is systematic review with article selection using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guide. The results of the article search, obtained 35 articles of Pubmed databes, then selected using critical appraisal assessment and obtained 5 articles that fit the inclusion category that includes the effectiveness of yoga interventions in iwa nurses who experience work stress. Conclusion of From the results of literature review some articles can be concluded that there are several interventions carried out on the work stress of mental nurses. and from the results of the review literature obtained the number of medical personnel in the mental care department who are stressed due to work, from the results of the review there are several interventions given to mental nurses related to work stress but which are effectively used. Yoga therapy has been shown to be effective in mental nurses or medical personnel who are stressed at work